Management of the stalked barnacle (Pollicipes pollicipes) fishery in the Nature Reserve of Berlengas (Portugal): evaluation of bag and size limit regulation measures. - Jacinto, D. (2012)
The stalked barnacle Pollicipes pollicipes (Gmelin, 1790) is an important shellfish resource in Portugal. Due to the social-economic importance of barnacle harvesting, a management plan aimed at achieving a controlled and sustainable activity (including temporal and spatial closures, rotational harvesting, a limited number of harvesting licenses, bag and size limits for catches and catch reporting) was implemented in 2000 at the Berlengas Nature Reserve (RNB) in central Portugal. We evaluated the bag and size limits imposed by the management plan, performing observations on harvesting activity and asking licensed harvesters and RNB staff about these measures. Both inquiries and observations suggest that licensed harvesters are not following the bag and size limits imposed. Mean amounts captured in RNB varied from 14 to 24 kg per harvester/day, but 25% of the observations corresponded to higher catches per individual than the total amount allowed (20 kg). Only half of the sampled amounts (taken in autumn 2005 and 2006) were in agreement with the size limit regulation and 50% of the total biomass comprised individuals of maximal rostro-carinal length (RC) ␣25 mm. For most harvesters, size limit is the most difficult management rule to fulfil. Both harvesters and RNB staff agree that surveillance is scarce and is a major problem of this fishing activity. In order to achieve a more sustainable use of this resource, we propose the implementation of a more effective surveillance and monitoring plan, the definition of a unique landing site, the maintenance of the bag limit (20 kg) and a reduction of the size limit (50% of total biomass comprising individuals ␣22 mm RC).